2002
DOI: 10.1111/1468-0297.00731
|View full text |Cite
|
Sign up to set email alerts
|

Inequality and Conservation on the Local Commons: A Theoretical Exercise

Abstract: To analyze the e ect of asset inequality on cooperation within a group, we consider a twoplayer noncooperative model of conservation of a common-pool resource CPR : a shery. W e give necessary and su cient conditions such that conservation is a Nash equilibrium, and we show that increasing inequality does not, in general, favor full conservation. However, once inequality is su ciently great, further inequality m a y push the players closer to e ciency. T h us the relationship between inequality and economic e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(65 citation statements)
references
References 20 publications
2
63
0
Order By: Relevance
“…In this way, the location of the resource influences the users to join in a collective effort. The reasons are highly consistent with various opinions expressed in the empirical literature, for example Bardhan (1993); Dayton- Johnson and Bardhan (1999);Agarwal (2002) and Araral (2009). They found that cooperation is more difficult when water is either very scarce (due to potential conflict on water allocation) or is plentiful (because of little incentive to cooperate, since water is abundant).…”
Section: A) Physical and Technical Characteristics Of The Resourcesupporting
confidence: 82%
“…In this way, the location of the resource influences the users to join in a collective effort. The reasons are highly consistent with various opinions expressed in the empirical literature, for example Bardhan (1993); Dayton- Johnson and Bardhan (1999);Agarwal (2002) and Araral (2009). They found that cooperation is more difficult when water is either very scarce (due to potential conflict on water allocation) or is plentiful (because of little incentive to cooperate, since water is abundant).…”
Section: A) Physical and Technical Characteristics Of The Resourcesupporting
confidence: 82%
“…But when there are very high levels of inequality, there is very low incentive for cooperative action due to either the vested interests of the rich users to deter collective action for personal gain or due to seasonal migration by the poor users, which undermines the sustainability of any cooperative action undertaken by the community (Molinas, 1998) 5 . 5 It should be noted that though the results obtained by Molinas (1998) seem contradictory to those obtained by Bardhan and Dayton Johnson (forthcoming) and Dayton-Johnson and Bardhan (2002) the former study the effect of heterogeneity on cooperation whereas the latter investigates the effect of heterogeneity on…”
Section: Complexities Of Heterogeneitymentioning
confidence: 92%
“…Dayton-Johnson and Bardhan (2002), for instance, show that the relationship between inequality and levels of collective action in conservation can be U-shaped in the fishery sector. Fishers who have outside earnings opportunities may believe that increased inequality has a negative effect on conservation.…”
Section: Elite Capture In Natural Resource Managementmentioning
confidence: 99%